Donor–Acceptor Viologens with Through‐Space Conjugation for Enhanced Visible‐Light‐Driven Photocatalysis - Yi Qiao; Liang Xu; Xiaoyang Liu; Yujing Gao; Naiyao Li; Yawen Li; Tianle Cao; Ni Yan; Zishun Liu; Gang He (Advanced Science)
Abstract A series of novel donor–acceptor (D–A) type viologens with through‐space conjugation (TSC) are synthesized. The synergistic effect of D–A conjugation and TSC endow these compounds with a narrower energy gap, excellent redox properties, strong absorption in the visible range (up to 450 nm), and high efficiency of intramolecular charge transfer (ICT). These compounds also exhibit a long‐lived charge separation state and stable radical formation. Considering their impressive photophysical and redox properties, TSC viologens with D–A conjugation are explored for visible‐light‐driven photocatalysis. As a catalyst in oxidative coupling reactions under visible light, compound 9 can achieve a yield of 94%, attributed to its strong ICT effect. Additionally, hybridized into graphitic carbon nitride (g‐C₃N₄), compound 9 enhances hydrogen production performance under visible light, achieving an H2 generation rate of 4102 µmol h−1g−1. This study highlights the potential applications of TSC viologens in photocatalytic systems.